Differential Effects of Oxytocin on Agency and Communion for Anxiously and Avoidantly Attached Individuals. (August 2015) - Bartz, Jennifer A.; Lydon, John E.; Kolevzon, Alexander; Zaki, Jamil; Hollander, Eric; Ludwig, Natasha; Bolger, Niall
Oxytocin promotes prosocial behavior, especially in those individuals who are low in affiliation (e.g., avoidantly attached individuals), but can exacerbate interpersonal insecurities in those preoccupied with closeness (e.g., anxiously attached individuals). One explanation for these opposing observations is that oxytocin induces a communal, other-orientation. Becoming more other oriented should help those people who focus on the self to the exclusion of others, but could be detrimental to those who are other focused but have little sense of an agentic self. Using a within-subjects design, we administered intranasal oxytocin and placebo to 40 males and measured their agency (self-orientation) and communion (other-orientation). Oxytocin produced a slight increase in communion for the average participant; however, as predicted, avoidantly attached individuals were especially likely to perceive themselves as more communal ("kind, " "warm, " "gentle, " etc.) after receiving oxytocin than after receiving the placebo. There was no main effect of oxytocin on agency for the average participant; however, anxiously attached individuals showed a selective decrease in agency ("independent, " "self-confident, " etc.) following administration of oxytocin. These data help explain the complex social effects of oxytocin.